2019
DOI: 10.3389/fvets.2019.00158
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Antimicrobial Use in Dutch Companion Animals

Abstract: Antimicrobial resistance (AMR) is an increasing threat, both in human and in veterinary medicine. To reduce the selection and spread of AMR, antimicrobial use (AMU) should be optimized, also in companion animals. To be able to optimize AMU, a feasible method to quantify AMU and information on current AMU are needed. Therefore, a method to quantify AMU was developed, using the number of Defined Daily Doses Animal (DDDA). This method was used to explore applied antimicrobial classes and to identify differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
3
25
0
3
Order By: Relevance
“…Therefore, comparisons of AMU and AMR levels between countries and species should be interpreted while keeping in mind the restrictions of this small sample size. Nevertheless, the results did show similar trends with previous studies [25,26,28,[45][46][47][48] and enabled the identification of some significant differences, although some might be missed due to a lack of power. A recent Dutch study reported on the many different factors influencing the antimicrobial prescribing behavior of veterinarians [52].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, comparisons of AMU and AMR levels between countries and species should be interpreted while keeping in mind the restrictions of this small sample size. Nevertheless, the results did show similar trends with previous studies [25,26,28,[45][46][47][48] and enabled the identification of some significant differences, although some might be missed due to a lack of power. A recent Dutch study reported on the many different factors influencing the antimicrobial prescribing behavior of veterinarians [52].…”
Section: Discussionsupporting
confidence: 86%
“…A study in the UK, using data from 374 veterinary practices, reported similar proportions of CIAs usage, 60% in dogs and 81% in cats [49]. The most frequently used antimicrobial agent and CIA for dogs and cats was amoxicillin-clavulanate, which corresponds to previous research [26][27][28]50,51].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…One potential explanation for the difference might be that use of extended spectrum cephalosporins (ESCs) is very limited in Sweden, while in the Netherlands, ESCs, i.e. cefovecin, was frequently used for companion animals [10,16]. The low usage in Sweden is partly due to a regulation implemented in 2013 which limits the veterinarians' right to prescribe ESCs, stating that these can only be used if alternative choices cannot be expected to be successful (The Swedish Board of Agricultures regulations on drugs and drug usages (In Swedish), SJVFS 2013:42, https ://www.jordb ruksv erket .se).…”
Section: Resultsmentioning
confidence: 99%